Challenges for the empowerment of young mental health service users in Norway - Marian , Ådnanes (International Journal of Psychosocial Rehabilitation, 2017)
Objective. The objective of this study was to explore how principles of empowerment are reflected in the experiences of young users of the mental health service in Norway and to determine challenges to their implementation. Method. Thirty-two qualitative interviews were conducted with nine users during a 12-month period and analyzed to identify key themes related to their empowerment. Results. Four themes were identified: the users’ wish to have control of their own illness and treatment; their trust in themselves and plans; at the same time, their self-devaluation and vulnerability; and a feeling of powerlessness because of the lack of choice and information within the Norwegian mental health service system. Conclusion. The young mental health service users in our study had an adequate level of psychological empowerment. However, their empowerment as mental health patients was restricted by environmental factors, most of all the skewed power distribution between users and health service professionals.